The Potential Negative Effect of a Lambda-Cyhalothrin Pesticide on Some Testicular Functions in Male Albino Rats - Al-Swefee, Duha Zeki (American Journal of Biology and Natural Sciences, 2025)
In this study, the triggered toxicity of the pyrethroid pesticide lambda-cyhalothrin (LCT) was investigated in male albino rats. The total number of adult’s rat applied in the experiment was Fifteen, separated into three groups and orally administered LCT at doses 0, 15, and 30 mg/kg for 30 days. Serum reproductive hormones, oxidative stress biomarkers, and sperm functional parameters were evaluated during the laboratory experiment. LCT exposure resulted in a significant elevation of prolactin levels, while estrogen remained unchanged. Two doses of LCT were applied, the result shows a highly significant reduction in FSH, LH, and testosterone concentrations, indicating disruption of the hypothalamic-pituitary-gonadal axis. Oxidative stress was markedly increased, as evidenced by elevated levels of malondialdehyde (MDA), catalase (CAT), glutathione (GSH). The laboratory tests of sperms indicated decline in total sperm count and motility, as well by increased percentages of dead and morphologically abnormal sperm in treated groups. These findings demonstrate that LCT induces pronounced endocrine disruption, oxidative imbalance, and deterioration of sperm quality, confirming its strong reproductive toxicity in male rats. The study emphasizes the potential risk of LCT exposure to male fertility and highlights the need for stricter regulation and reduced environmental use of pyrethroid pesticides.